Carbon-oxygen isotopes and rare earth elements as an exploration vector for Carlin-type gold deposits: A case study of the Shuiyindong gold deposit, Guizhou Province, SW China. (15th October 2017) - Tan, Qin-Ping; Xia, Yong; Wang, Xueqiu; Xie, Zhuo-Jun; Wei, Dong-Tian
Graphical abstract: Highlights: Calcites enriched in 18 O and depleted in 13 C distribute along orebodies and fault. Calcites with MREE enrichment mainly occur around orebodies. Calcite is a useful indicator for blind gold ores in southwestern Guizhou Province. Abstract: The Shuiyindong gold deposit is a deeply concealed strata-bound Carlin-type deposit in southwestern Guizhou Province, China. The deposit lies on the eastern limb of the Huijiabao anticline with ores mainly along the anticline axis and hosted in bioclastic limestone, containing calcite veins, of the Permian Longtan Formation units. In this study, we measured carbon and oxygen isotopic ratios and rare earth element (REE) concentrations of the host rocks and calcite veins along a profile across the Shuiyindong deposit. Orebodies in the upper unit of the Longtan Formation have higher δ 18 O values (20.6–22.4‰) and lower δ 13 C values (−3.7 to −0.5‰) than the country rocks (δ 18 O: 18.8–21.4‰; δ 13 C: −0.7 to 0.8‰). However, there are no obvious trends of δ 18 O and δ 13 C values from the country rocks to the orebodies in the middle unit of the Longtan Formation. The spatial distribution of the calcite veins displays distinct halos of δ 13 C and δ 18 O values and REE concentrations. Calcite veins along the anticlinal axis and major reverse fault are enriched in Middle REE (Sm, Eu, Gd, and Tb) and 18 O and depleted in 13 C. Surficial veining calcite-filled fractures/faults that connect to deep concealed strata-bound gold mineralization systems can be vectors toward deep ores in southwestern Guizhou Province, China.